Complete mitochondrial genome of the pink bollworm Pectinophora gossypiella (Lepidoptera: Gelechiidae). (3rd May 2016) - Zhao, Jing; Sun, Yang; Xiao, Liubin; Tan, Yongan; Dai, Hanyang; Bai, Lixin
Abstract: Pectinophora gossypiella (Lepidoptera: Gelechiidae) is a key pest in many cotton-growing countries of the world. In this study, the complete mitochondrial (mt) genome of the pink bollworm P. gossypiella was determined, which is 15, 202 bp in length (GenBank accession number: KM225795) containing 37 typical animal mitochondrial gene and an A + T-rich region. The gene order of P. gossypiella mtDNA was different from the insect ancestral gene order in the translocation of trnM, as shared by previously sequenced lepidopteran mtDNAs. The protein-coding genes (PCGs) have typical mitochondrial start codons ATN, with the exception of COI, Nad5, which uses the start codons CGA, GTT. Eight PCGs stop with complete termination codons (TAA), whereas five PCGs use incomplete stop codon T. All of the tRNA genes had typical cloverleaf secondary structures except for trnS1(AGN), in which the dihydrouridine (DHU) arm did not form a stable stem-loop structure. Like other insects, the control region is located between rrnS and trnM with a length of 309 bp and an A + T content of 94.8%, which is the most AT-rich region and comparatively simple, with little evidence of long tandem repeats, but harbors a conserved structure combining the motif ATAGA and a 18-bp poly-T stretch.